Macbeth : language and writing - Smith, Emma (Emma Josephine) (London : Bloomsbury, 2013)
Arden Student Guides: Language and Writing offer a new type of study aid which combines lively critical insight with practical guidance on the critical writing skills you need to develop in order to engage fully with Shakespeare's texts. The books' core focus is on language: both understanding and enjoying Shakespeare's complex dramatic language, and expanding your own critical vocabulary, as you respond to his plays. Key features include: an introduction considering when and how the play was written, addressing the language with which Shakespeare created his work, as well as the generic, literary and theatrical conventions at his disposal; detailed examination and analysis of the individual text focusing in it literary, technical, and historical intricacies; discussion of performance history and the critical reception of the work. At a climactic point in the play, Macbeth realises that the witches have deceived him through their ambiguous language:'they palter with us in a double sense'. This book explores Shakespeare's own paltering in the play - the densely rich language of ambition, of blood, and of guilt that structures Macbeth. -- Provided by publisher.
Includes bibliographical references.
Keywords: Shakespeare, William, -- 1564-1616.; Shakespeare, William, -- 1564-1616 -- Language